Decreased consumption of rewarding sucrose solutions after injection of melanocortins into the ventral tegmental area of rats - Yen, Haw-Han; Roseberry, Aaron G. (Psychopharmacology, 2015)
Rationale The mesolimbic dopamine system is an important component of the neural circuitry controlling reward-related behavior. We have recently shown that the melanocortin peptides decrease normal homeostatic feeding through actions in the ventral tegmental area. It is unknown, however, whether melanocortin peptides can also act on dopamine pathways to regulate hedonic, reward-related aspects of feeding. Objectives In these studies, we tested whether injection of melanocortin receptor agonists directly into the ventral tegmental area (VTA) affected the intake of appetizing and rewarding sugar solutions in two-bottle choice tests. Methods Varying doses of the melanocortin receptor agonist, MTII, were injected into the VTA, and the intake of different sugar solutions was measured in two-bottle choice tests to distinguish between potential effects on homeostatic versus hedonic aspects of feeding. In addition, 24-h food intake was measured throughout the experiments. Results Injection of MTII into the VTA dose dependently decreased the intake of 1 and 2 % sucrose solutions and 0.2 % saccharin solutions and decreased 24-h food intake in each study. Although MTII also decreased the intake of a 10 % sucrose solution, MTII appeared to be less potent in rats exposed to 10 % sucrose, as only the highest dose of MTII tested was effective at reducing 10 % sucrose intake and food intake in these rats. Conclusions These studies demonstrate that melanocortins can act directly in the VTA to control reward-related feeding. Thus, these studies add to the growing body of evidence showing that melanocortins can interact with the mesolimbic dopamine system to regulate multiple reward-related behaviors.